Evaluation and Correction of the Ambient Particle Spectral Light Absorption Measured Using a Filter-based Aethalometer - Gang Zhao; Yingli Yu; Ping Tian; Jing Li; Guo Song; Chunsheng Zhao (Aerosol and Air Quality Research)
Abstract Spectral light-absorption properties measured with an Aethalometer (AE; Model AE33; Magee Scientific) are widely used in radiative forcing studies and source appointment in China. However, considerable uncertainty regarding the measured absorption coefficient (σabs) exists because of the multiple-scattering effects, loading effects, and differences in filter tape. This study evaluated σabs by comparing the values measured with an AE33 using Tape 8050, an AE33 using Tape 8060 (which differs from Tape 8050 in material), and a three-wavelength photoacoustic soot spectrometer (PASS-3) during two field campaigns in eastern China. The results indicated that the AE33-measured σabs using either tape exceeded the PASS-3-measured value by approximately three times, mainly owing to the multiple-scattering effect. A wavelength-independent multiple-scattering compensation factor (2.90), which varies slightly (± 0.04) for eastern China, is recommended for these regions. When σabs was measured with the AE33 using Tape 8050, the value highly depended on the loading on the tape, which led to significant uncertainty and discontinuity in the absorption Å ngström exponent compared to using Tape 8060. A method was proposed to effectively correct the historical datasets of σabs and the absorption Å ngström exponent by using the AE33 with Tape 8050. This work provides insight into the quality of measured absorption data when filter-based measurement technology is applied.